Diversion of the Arbuzov reaction: alkylation of C–Cl instead of phosphonic ester formation on the fullerene cage. Issue 30 (6th June 2019) - Kraevaya, Ol'ga A.; Peregudov, Alexander S.; Troyanov, Sergey I.; Godovikov, Ivan; Fedorova, Natalya E.; Klimova, Regina R.; Sergeeva, Vasilina A.; Kameneva, Larisa V.; Ershova, Elizaveta S.; Martynenko, Vyacheslav M.; Claes, Sandra; Kushch, Alla A.; et al.
Abstract : We report an "inversed" Arbuzov reaction of C60 Ar5 Cl with P(OR)3 producing C60 Ar5 R with an excellent selectivity. Abstract : We report an "inversed" Arbuzov reaction of the fullerene derivatives C60 Ar5 Cl with trialkyl phosphites P(OR)3 producing alkylated fullerene derivatives C60 Ar5 R (R = Me, Et, iPr, n Bu) with almost quantitative yields. This reaction provides a convenient synthetic route for the preparation of a large variety of functionalized fullerene derivatives with tailored properties, e.g. water-soluble compounds demonstrating promising antiviral activities against HCMV, HSV1, HIV and several influenza virus strains.